Chemical additives enhance the activity of a Bt‐based biopesticide targeting the beet webworm larvae - Opisa, S.; Akutse, K.S.; Plessis, H. du; Fiaboe, K.K.M.; Ekesi, S. (Wiley, 2020)
Spoladea recurvalis (Fbr.) (Lepidoptera: Crambidae) larvae can cause up to 100% foliage loss on amaranths during severe outbreaks. The Bacillus thuringiensis Subsp. kurstaki product Halt® is a biologically safe biopesticide recommended for the management of Spodoptera exigua (Hübner) and Plutella xylostella (Linnaeus). Spoladea recurvalis larvae are less susceptible to the product. Thirteen chemical additives to improve the efficacy of a Bt spray for control of S. recurvalis were evaluated in laboratory bioassays against second‐instar larvae. All the additives except calcium chloride caused an increase in mortality when applied in mixtures with Bt. Among the seven inorganic salts, boric acid was the only inorganic acid that caused more than 50% larval mortality. Boric acid at a concentration of 0.05% increased the activity of B. thuringiensis by 2.9‐fold. Boric acid had the shortest LT50 values of 5.3 days compared with all other combinations. Two nitrogenous compounds, peptone and sodium nitrate, caused 54 and 51% larval mortalities; however, this increase in efficacy was not significantly different from the mortalities caused by Bt applied without any additive. Urea increased larval mortality from 40% to 51%, although the increase was not significant from a Bt spray application only. Citric acid had no significant effect on the efficacy of Bt spray against S. recurvalis larvae. Overall, among the additives evaluated, the efficacy of Bt spray was most enhanced by boric acid and could be further evaluated under field conditions for validation, and integration into an Integrated Pest Management (IPM) strategy for S. recurvalis management.